The intercultural educator: the what, how, and why of teaching intercultural communicative competence in Latin America (Revista Innova Educación, 2022)
A reflective assessment of teaching praxis’ notions and beliefs becomes essential in instructing learners to effectively interact in intercultural encounters. Arguments in favor of teaching the intercultural component have been promoted for years but have not fully reached systematic incorporation in foreign language education in Latin American countries. This paper examines the concept of the intercultural mediator, approaching key questions (why, what, and how) that emerge when integrating intercultural objectives in the language classroom supported on theoretical frameworks and insights from the authors’ teaching experience. The methodology used was an exploratory qualitative document review. Scientific articles published in reliable databases were consulted to answer the questions targeting intercultural communicative competence teaching. The main objective is to invigorate the discussion regarding the intercultural component in the classroom while exploring practical ideas to teach it. Findings suggest that there is a growing body of literature and interest on approaching theoretical and practical standpoints toward ICC guiding teachers to become intercultural educators willing to integrate and enable learners with the crucial ICC competence. Educators can make a difference in the classroom by utilizing different Latin American resources and material to mediate intercultural matters in the foreign language classroom.
Keywords: Foreign language; intercultural competence; mediator; teaching